Personality patterns of elementary and high school teachers in relation to efficiency ratings - Oducado, Yolanda O. (Animo Repository, 1978)
This is a study of personality characteristics and attitudes of the elementary and high school teachers of one school run by the Missionary Sisters of the Immaculate Conception (MIC). Likewise, it establishes the relationship between certain personality characteristics and attitude of teachers and their bearing on efficiency. The research design used was descriptive and analytical. The subjects were composed of 51 teachers for the school year 1976-1977, 15 of whom were high school teachers, and 36 elementary teachers. The study used the following instruments : 1. Comrey Personality Scale (CPS), 2. Teacher Attitude Inventory (TAI), 3. Teaching Efficiency Rating Scale (TERS), and 4. Personal Data Sheet. Statistical tools used were frequency ranks, percentages, means, standard deviations, Pearson Product-Moment Correlation and Multiple Correlation and Regression Analysis. Based on the findings, the following conclusions were drawn : 1. The teachers of the Immaculate Conception Academy of Manila (ICAM) tended to manifest normal personality characteristics, have healthy attitude toward teacher-pupil relations and are more than average in their efficiency rating. 2. The teachers have healthy attitude towards modern methods and approaches in teaching, as revealed by the item analysis of the TAI. 3. Emotional stability, orderliness, activity, teacher attitude, educational qualification, educational level taught and tenure are significant multiple correlates of reaching efficiency, and they contribute considerably to the assessment value of teacher efficiency.